Physico-chemical characterization of succinyl chitosan-stabilized liposomes for the oral co-delivery of quercetin and resveratrol. (10th February 2017) - Caddeo, Carla; Pons, Ramon; Carbone, Claudia; Fernàndez-Busquets, Xavier; Cardia, Maria Cristina; Maccioni, Anna Maria; Fadda, Anna Maria; Manconi, Maria
Highlights: Chitosan was succinylated and used to form a protective shell onto liposomes. Succinyl-chitosan liposomes were conceived for the oral delivery of quercetin and resveratrol. Succinyl-chitosan increased the physical stability of the vesicular system. Succinyl-chitosan increased the release of the polyphenols at intestinal pH. Abstract: In the present work, quercetin and resveratrol, natural polyphenols with strong antioxidant and anti-inflammatory properties, were co-loaded in polymer-associated liposomes conceived for oral delivery, by exploiting the potential of pH-sensitive succinyl-chitosan. Chitosan was succinylated, characterized by Nuclear Magnetic Resonance spectroscopy and Gel Permeation Chromatography, and used to form a protective shell on the surface of liposomes. The physico-chemical properties of the succinyl-chitosan liposomes were assessed by light scattering, zeta potential, cryogenic transmission electron microscopy, and small angle X-ray scattering. Small, spherical, uni- and bilamellar vesicles were produced. The succinyl-chitosan shell increased not only the physical stability of the vesicular system, as demonstrated by accelerated stability tests, but also the release of the polyphenols to a greater extent at pH 7.0, mimicking the intestinal environment. The proposed approach based on polyphenol vesicular formulations may be of value in the treatment of pre-cancerous/cancerous intestinal conditions associated with inflammation and oxidative stress.